Multi-objective parametric optimization for high surface quality and process efficiency in micro-grinding. (May 2021) - Wang, Jun; Ye, Qiang; Zhao, Man; Shi, Xusheng; Fei, Tingwei
In this study, for the selection of maximum material removal rate and minimum surface roughness( R a ) in micro-grinding of aluminum alloy through multi-response optimization, two optimization approaches are proposed based on statistical analysis and genetic algorithm. The statistical analysis–based approach applies response surface methodology according to the analysis of variance to propose a mathematical model forR a . In addition, the individual desirability of material removal rate, R a, and the global desirability function are calculated, and the inverse analysis is conducted to locate input setting giving maximum desirability function. The genetic algorithm–based approach uses the improved multi-objective particle swarm optimization with the experimental data trained by support vector machine. To demonstrate that the material microstructure is a significant parameter for material removal rate andR a, the models with and without Taylor factor consideration are developed and compared. The optimized results achieved from both response surface methodology and improved multi-objective particle swarm optimization demonstrate that the consideration of Taylor factor can significantly improve the optimization process to achieve the maximum material removal rate and minimumR a .